Strategi Komunikasi Publik Badan Penyelenggara Jaminan Produk Halal dalam Sosialisasi Sertifikasi Halal di Media Sosial - Djamaluddin, Muhammad; Darajat, Deden Mauli; Rahmi, Cinta (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2024)
This paper describes how the public communication strategy carried out by the Halal Product Guarantee Agency (BPJPH) in socializing halal certification on Instagram social media. BPJPH on social media conducts socialization in various ways. The communication strategy carried out is first, strengthening in terms of content or content of messages distributed by BPJPH in the socialization of halal certification. Second, activities carried out by BPJPH in terms of socializing halal certification are loaded with various stories on social media. Third, BPJPH also invites various institutions, both universities and non-governmental organizations (NGOs) to become agents in the socialization of halal certification and uploaded on BPJPH social media. Halal certification socialized by BPJPH is a program related to certified halal products needed by the Muslim community in particular and the Indonesian people in general.